2017
DOI: 10.1590/0037-8682-0462-2016
|View full text |Cite
|
Sign up to set email alerts
|

Case report of myeloperoxidase deficiency associated with disseminated paracoccidioidomycosis and peritoneal tuberculosis

Abstract: Myeloperoxidase (MOP) is present in monocyte and neutrophil lysosomes, catalyzing hydrogen peroxide and chloride ion conversion to hypochlorous acid. MOP seems to destroy pathogens during phagocytosis by neutrophils and is considered an important defense against innumerous bacteria. We present a patient who had MOP deficiency, who presented with a subacute form of paracoccidioidomycosis and later with peritoneal tuberculosis. MOP deficiency leads to the diminished destruction of phagocytized pathogens. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…MPO deficient leukocytes still mounted an efficient oxidative response and a candida-static effect [30]. Other cases of prolonged infection have been reported since then [31]. The first larger epidemiological study compared 92 cases of MPO deficient individuals to a matched control group and revealed an association of MPO deficiency with increased occurrence of infectious complications and higher prevalence of chronic inflammatory disease, specifically arthritis [32].…”
Section: Introduction Mpo Conservation Across Species Maturation In Myeloid Progenitors and Its Role In Immune Responsesmentioning
confidence: 99%
“…MPO deficient leukocytes still mounted an efficient oxidative response and a candida-static effect [30]. Other cases of prolonged infection have been reported since then [31]. The first larger epidemiological study compared 92 cases of MPO deficient individuals to a matched control group and revealed an association of MPO deficiency with increased occurrence of infectious complications and higher prevalence of chronic inflammatory disease, specifically arthritis [32].…”
Section: Introduction Mpo Conservation Across Species Maturation In Myeloid Progenitors and Its Role In Immune Responsesmentioning
confidence: 99%
“…We think that tuberculosis may contribute to the unmasking of PCM in cases of co-infection, since the association of both diseases and its severe presentation may be associated with the deficiency of some proteins responsible for the immune response such as myloperoxidase, an enzyme present in the lysosomes of monocytes and neutrophils that catalyzes the conversion of hydrogen peroxide and chloride ion into hypochlorous acid and thus destroy these pathogens during the process of phagocytosis by neutrophils and is considered an important defense against countless bacteria [16] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ]. MPO is an enzyme present in the lysosomes of monocytes and neutrophils, and it catalyzes the formation of reactive oxygen intermediates, including hypochlorous, hypobromous, and hypothiocyanous acids [ 63 ], and has been implicated in TB response [ 64 , 65 ]. Finally, the KCNMA1 gene (potassium calcium-activated channel subfamily M alpha 1) was recently reported by Tabone O., et al .…”
Section: Discussionmentioning
confidence: 99%
“…MPO (Myeloperoxidase) was first reported to be involved in LTBI by Kaforou M., et al [62]. MPO is an enzyme present in the lysosomes of monocytes and neutrophils, and it catalyzes the formation of reactive oxygen intermediates, including hypochlorous, hypobromous, and hypothiocyanous acids [63], and has been implicated in TB response [64,65]. Finally, the KCNMA1 gene (potassium calciumactivated channel subfamily M alpha 1) was recently reported by Tabone O., et al [23] to be involved in the clinical TB stage, and was also related to TB in vivo studies of gene expression of lung granulomas isolated from sham-vaccinated nonhuman primates at 10 weeks after infection with M. tuberculosis [66].…”
Section: Plos Onementioning
confidence: 99%